Reincarnation and Identity: A Multidisciplinary Exploration of Druze Narratives: Book Forum: Druze Reincarnation Narratives: Previous Life Memories, Discourses, and the Construction of Identities, by Gebhard Fartacek (ed.) - Natoor, Maha; Sevruk, Dmitry; Kreinath, Jens; Fartacek, Gebhard (Druze Studies Journal, 2024)
The book Druze Reincarnation Narratives: Previous Life Memories Discourses and the Construction of Identities, edited by Gebhard Fartacek, offers an interdisciplinary exploration of the Druze belief in reincarnation (taqammuṣ) and the phenomenon of Nutq, where individuals recall previous lives. Scholars in anthropology, religious studies, and related fields contribute to understanding how these beliefs shape Druze social structures, personal identities, and community cohesion. The forum includes reviews by Maha Natoor, Dmitry Sevruk, and Jens Kreinath. Natoor appreciates the book’s accessibility and balanced presentation of Druze reincarnation narratives while raising ethical concerns about anonymity and the use of religious texts. Sevruk commends the clear scientific language and interdisciplinary approach, emphasizing the book’s contributions to Druze history and culture and suggesting further exploration of the psychological mechanisms behind reincarnation beliefs. Kreinath praises the detailed ethnographic insights and methodological rigor, noting researchers’ challenges in engaging with the Druze community. He also critiques that some contributions focus on broader social, cultural, and political contexts rather than directly addressing reincarnation. Overall, the book provides valuable insights into the resilience and adaptability of the Druze in preserving their unique religious identity amidst broader societal changes.